A systematic review of evaluating the efficacy of acne scar treatment by Fractional Laser with or without using adjunctive treatments. (18th August 2021) - Ghazzawi, Raghad; Hamadah, Omar
ABSTRACT: Fractional laser (FL) resurfacing has proved its effectiveness in acne scars treatments. To evaluate the efficacy of Fractional laser systems for treatment of acne scars as a monotherapy, and as adjunctive therapy with other treatment types. A systematic literature review was performed by searching the electronic databases PubMed, Google Scholar, and Embase. Fractional laser has proven therapeutic efficacy of over 26% in treating acne scars, with minor and transient side effects, and well-tolerant pain. The application of PRP not only accelerated recovery and reduced adverse events, but also enhanced localized collagen neogenesis and redistribution. The addition of surgical treatments to Fractional Laser Systemes (FLS) therapy delivers the best treatment results for Icepick scars. Fractional laser is an effective tool for treating acne scars. The degree of effectiveness varies according to the laser parameters, the number of treatment sessions, skin photo type, the severity and the type of scars. The application of Platelet-Rich Plasma (PRP) and Fractional Radiofrequency Microneedle (FRM) in addition to the FL treatment improves the therapeutic efficacy and reduces the appearance of Post Inflammatory Hyper-Pigmentation (PIH), and is the ideal treatment for dark-skinned patients. FL therapy along with surgical methods such as subsicion and punch techniques provided the best improvements for deep scars.